2021
DOI: 10.3389/fimmu.2021.618577
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Envelope Protein Domain III Induces Nlrp3 Inflammasome-Dependent NETosis-Mediated Inflammation in Mice

Abstract: Abnormal immune responses and cytokine storm are involved in the development of severe dengue, a life-threatening disease with high mortality. Dengue virus-induced neutrophil NETosis response is associated with cytokine storm; while the role of viral factors on the elicitation of excessive inflammation mains unclear. Here we found that treatments of dengue virus envelope protein domain III (EIII), cellular binding moiety of virion, is sufficient to induce neutrophil NETosis processes in vitro and in vivo. Chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 105 publications
(68 reference statements)
2
44
0
Order By: Relevance
“…To verify these pyroptosis results using different methods, we performed additional caspase-1 colorimetric assay, detections of cleaved GSDMD and cell-surface GSDMD levels, and the releases of IL-1β and LDH. Consistently, inflammasome inhibitors Z-WHED-FMK, OLT1177, and pyroptosis/GSDMD inhibitor DMF ( 14 , 50 ) markedly rescued rEIII-induced pyroptosis and damages of platelets ( Figures S11 , S12 ). These results collectively suggest that EIII induced an Nlrp3 inflammasome-dependent pyroptosis in platelets.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…To verify these pyroptosis results using different methods, we performed additional caspase-1 colorimetric assay, detections of cleaved GSDMD and cell-surface GSDMD levels, and the releases of IL-1β and LDH. Consistently, inflammasome inhibitors Z-WHED-FMK, OLT1177, and pyroptosis/GSDMD inhibitor DMF ( 14 , 50 ) markedly rescued rEIII-induced pyroptosis and damages of platelets ( Figures S11 , S12 ). These results collectively suggest that EIII induced an Nlrp3 inflammasome-dependent pyroptosis in platelets.…”
Section: Resultssupporting
confidence: 53%
“…Here we found that in agreement with platelet activation data ( Figures 1 and S3 – S5 ), treatments with DENV and rEIII induced platelet cell death in a dose-dependent manner ( Figure 3A ). Various cell death inducers, including nigericin (pyroptosis), doxorubicin (apoptosis), rapamycin (autophagy), TNF- α (necroptosis), and erastin (ferroptosis) roughly induced the respective cell death pathway of tested platelets ( Figure 3B , RCD % of total cells; 3C, RCD % of total dead cells; Figure S9 , flow cytometry gating and calculations) ( 13 , 14 ). Intriguingly, when compared with these cell-death agonists, treatments with DENV and rEIII induced considerable pyroptosis, necroptosis, and ferroptosis responses of platelets but only minor levels of apoptosis ( Figures 3B, C ) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This NET formation was alleviated in neutrophils from NLRP3 inflammasome-deficient mice, decreasing inflammation. Blocking EIII-neutrophil interactions also suppressed the NETosis [83].…”
Section: Dengue Virusmentioning
confidence: 89%